Notes on ethno-pragmatics as a device for inter-cultural communication intelligence (ICQ) - Ahmad, Che Mahzan (Versita, Warsaw, 2011)
Ethno-pragmatics as device to understand the culturally Other is essential when we believe that there is a nexus of intimate relationships between language and culture. The whole idea of ethno-pragmatics is to understand local life-worlds in the wake of celebrating particularism in inter-cultural communication. Ethnopragmatics basically appreciates language practices in terms that make sense to the people concerned, whether in terms of indigenous values, beliefs, attitudes, social categories or emotions, and so on. Understanding cultural keywords is pertinent in ethno-pragmatics. These living words provide the best key to a culture’s values and assumptions, and they are embedded in the cultural scripts of the society/community. With the above positioning, we suggested that ethno-pragmatics be the device for intercultural communication intelligence (ICQ). In this work we employed a cultural script quest in order to capture/understand the tapestry of Malay culture. Bahasa (“language”) is one of the main Malay cultural keywords. The Malays relate bahasa to various norms and beliefs that encompass their life-world. Bahasa is molecularly related to their emotions, sense-making and aesthetics. As an illustration, we provide ICQ-at-work with halus as a technique of utilizing bahasa for successful speech-acts. Specifically, we narrate on Malay “indirectness” as a way of having conversation with the culturally Other.